ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA MENGGUNAKAN METODE BOW TIE DI PT. X - Permata, Ekie Gilang (Program Studi Kesehatan dan Keselamatan Kerja, 2020)
The palm oil mill industry has many risks to occupational safety and health. There are still many work accidents that occur resulting in losses for the company. Therefore, it is necessary to do a risk analysis wit importance index that assesses risk by considering the frequency index and severity index. Risk assessment is carried out by experts namely mill manager, mill assistants, and foreman. Then the risk identification is done based on the cause and effect of the risk using the Bow Tie method. Risk assessment indicators use risk indicators from palm oil mills. From 54 risk indicators, there is 3 significant risk, namely, employees exposed to hot iron (stew operation), employees inhaled /exposed to chemicals (WTP operation), noise (engine room operation). And there are 2 high risks, namely employees exposed to steam to hot steam (stew operation), employees exposed to fire bursts (boiler operation). The causes of significant and high risks are leaking pipes, opening the stew doors when high pressure, stew doors are not tightly closed, employee negligence, employees do not obey work instructions, high air pressure, lack of noise absorbent, material, there are worn, engine parts. The impact of significant and high risk burns to the skin, material loss, shortness of breath, skin irritation, communication, disorders, damage to hearing. Control of significant and high risk using a complete PPE, providing evacuation tools.